NEUROTOXIC EFFECTS OF ORGANOPHOSPHORUS COMPOUNDS - Djumaniyazov Shavkat Atanazarovich (Journal of Science in Medicine and Life, 2024)
Irreversible inhibition of acetylcholinesterase (AChE) in the nervous system causes cholinergic syndrome during acute exposure to organophosphorus compounds (Goncharov N.V.; 2023). However, according to the researchers, it is assumed that other mechanisms of action specific to these compounds contribute not only to the acute toxicity of high doses of these insecticides, but also to the neurotoxic effects that develop after prolonged exposure to low doses, especially in the developing brain (Djumaniyazov Sh.A. 2022-2024). Based on the concept that AChE is the primary molecular target responsible for the acute toxicity of organophosphorus (OP) species, the LD50 of these insecticides should directly correlate with their IC50 for enzyme inhibition and/or the rate of reactivation of the inhibited enzyme. AChE inhibition is a common mechanism underlying OP neurotoxicity to the nervous system, and it can be predicted that exposure of a developing organism to any OP will cause exactly the same effect with a biological gradient proportional to the degree of inhibition of AChE activity. Exposure of developing organisms to different OPs causes different effects. Numerous studies have demonstrated that chlorpyrifos (CPF) can directly interact with and alter the activity of serine hydrolases, including carboxylesterases, muscarinic receptors, cannabinoid receptors, and structural proteins such as tubulin (Basharina A. A.; 2022).